2007
DOI: 10.1038/sj.bjc.6603672
|View full text |Cite
|
Sign up to set email alerts
|

Targeting homeostatic mechanisms of endoplasmic reticulum stress to increase susceptibility of cancer cells to fenretinide-induced apoptosis: the role of stress proteins ERdj5 and ERp57

Abstract: Endoplasmic reticulum (ER) malfunction, leading to ER stress, can be a consequence of genome instability and hypoxic tissue environments. Cancer cells survive by acquiring or enhancing survival mechanisms to counter the effects of ER stress and these homeostatic responses may be new therapeutic targets. Understanding the links between ER stress and apoptosis may be approached using drugs specifically to target ER stress responses in cancer cells. The retinoid analogue fenretinide [N-(4-hydroxyphenyl) retinamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 42 publications
3
115
2
4
Order By: Relevance
“…45 In cutaneous metastatic melanoma, we have recently demonstrated the clinical potential of ER stress-induced apoptosis, with BRAF wt melanomas showing greater sensitivity, compared with tumours harbouring hyperactivating mutations in the BRAF protein kinase. 32,33 Moreover, we have also shown (and confirmed in the present study) that BRAF mutation is associated with increased levels of basal autophagy. 20 Interestingly, ER stress-induced apoptosis is reduced in melanoma cells harbouring oncogenic BRAF compared with the observed induction in BRAF wt melanoma cells, and in this context and in contrast to observations in BRAF mutant melanoma cells, we have also shown that autophagy inhibition significantly sensitizes BRAF wt melanoma cells to ER stressmediated apoptosis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…45 In cutaneous metastatic melanoma, we have recently demonstrated the clinical potential of ER stress-induced apoptosis, with BRAF wt melanomas showing greater sensitivity, compared with tumours harbouring hyperactivating mutations in the BRAF protein kinase. 32,33 Moreover, we have also shown (and confirmed in the present study) that BRAF mutation is associated with increased levels of basal autophagy. 20 Interestingly, ER stress-induced apoptosis is reduced in melanoma cells harbouring oncogenic BRAF compared with the observed induction in BRAF wt melanoma cells, and in this context and in contrast to observations in BRAF mutant melanoma cells, we have also shown that autophagy inhibition significantly sensitizes BRAF wt melanoma cells to ER stressmediated apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…As shown in Figure 2a, BRAF V600E melanoma cell lines displayed approximately twofold greater expression of mRNA coding for ERdj5, ERp57, ATF4 and Xbp-I 33 compared with BRAF wt cells, indicating that a mild but consistent induction of ER stress is conferred by an activating mutation in the BRAF protein kinase. 28,32,33 To rule out the possibility that differences in ER stress induction were due to effects other than BRAF mutation, we expressed constitutively active BRAF V600E in the BRAF wt SKMel-110 melanoma cell line in order to compare melanoma cells with identical genetic background except for BRAF status. Cells stably expressing BRAF V600E or GFP were selected for more than 1 month in culture, in order to better represent in vivo tumour development and adaptation to BRAF activating mutation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that ER60 protease, an endoplasmic reticulum chaperone protein , is involved in endoplasmic reticulum stress response (Corazzari et al, 2007;Ni and Lee, 2007) and promotes tumor cell survival in hypoxic microenvironment brought about by poor vascularization (Koumenis, 2006).…”
Section: Er60 Protease and Breast Cancer Proliferationmentioning
confidence: 99%